Sympathetic skin response and R-R interval variation in cases with rheumatoid arthritis - (:unkn) unknown (My University, 2003)
To investigate the autonomic nervus system involvement in cases with rheumatoid arthritis (RA) by assesing sympathetic skin response (SSR) and R-R interval variation (RRIV), 14 healthy women and 10 women with RA, all of them without clinic dysautonomies were examined. SSR's were recorded palmar surface of both hands and soles of both feet, after stimulating median and tibial nerves individually. RRIV's were assessed at rest and during six deep breathing in one minute with electrodes placed on dorsal surfaces of both hands. SSR could not be obtained from lower extremities of one case with RA. We could not find any significant difference between two groups in terms of SSR latencies. RRIV values obtained during deep breathing to those recorded at rest (D%/R%) was found to be significantly lower in RA cases than healthy controls. RRIV values increased with deep breathing in healthy subjects, while they decreased in 50% of the RA cases. We conclude that assessment of SSR and RRIV are voluble methods for revelation of subclinical autonomic involvement in cases with RA.
Keywords: R-R interval variation; Rheumatoid arthritis; Sympathetic skin response